Acute Ischemic Stroke Following A Single Wasp Sting: The Impact of Early Intensive Multidisciplinary Rehabilitation (A Case Study): A Rare Presentation with Favorable Rehabilitation Outcome - Sasirekha K; Priya J; Ganesan B; Arun B (CV Media Inti Teknologi, 2026)
Background: Cerebrovascular accidents following Hymenoptera stings are exceptionally rare, with most reported cases involving multiple stings. This case study presents an unique case of acute ischemic stroke triggered by a single wasp sting and highlights the critical role of early intensive physiotherapy in achieving excellent functional recovery.Case Presentation: A 55-year-old previously healthy electricity lineman sustained a single wasp sting over the neck. After initial symptomatic treatment at a primary health center, he returned to work but collapsed within two hours, presenting with right side weakness, mild aphasia, and apraxia. Brain imaging showed subtle small-vessel ischemic changes without large-vessel occlusion. Extensive thrombophilia and cardioembolic workups were normal. The stroke was attributed to venom-induced vasospasm and inflammatory/thrombogenic effects. The patient was managed with intravenous corticosteroids, dual antiplatelet therapy, and low-molecular-weight heparin. Structured inpatient physiotherapy commenced on the patient who stays in the wards, good progression was noted as the day passes.Results: At the time of discharge the patient was walked with minimal assistance. At one-month follow-up, he achieved modified independence in activities of daily living, with ongoing gradual recovery of hand function. Functional Independence Measure (FIM) on admission it was 13, later it improved to 39 at the time of discharge, and the follow-up of the patient rose to 52. scores improved markedly since the admission to the follow-up.Conclusion: This case demonstrates that even a single wasp sting can precipitate acute ischemic stroke via vasospasm and inflammation. Prompt medical stabilization combined with early, intensive, goal-directed physiotherapy can yield rapid and substantial functional recovery.